PHYTOCHEMICAL, ANTIMICROBIAL, RADICAL SCAVENGING AND IN- VITRO BIOLOGICAL ACTIVITIES OF TEUCRIUM STOCKSIANUM LEAVES - Gul Rahim; Rahmatullah Qureshi; Ali Hazrat; Bashir Ahmad; Ayaz Ali Khan; Tari Aziz; Metab Alharbi; Abdulrahman Alshammari (Journal of the Chilean Chemical Society, 2023)
Teucrium stocksianum is locally used as home remedy in different parts of the world for the treatment of digestive problems as well as microbial infections. The present study was designed to screen phytochemical constituents and in vitro antimicrobial as well as radical scavenging activities of the leaves extracts from the Teucrium stocksianum. Methods: Plant samples of the Teucrium stocksianum were collected from the growing locality and four different solvents viz., n-hexane, methanol, ethanol, and water were used for the preparation of plant extracts. The in vitro biological activities were investigated against eight human pathogens such as like Bacteria: Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogen, Escherichia coli, Klebsiella pneumoniae and Pseusdomonas aeruginosa and Fungi: Aspergillus niger and Aspergillus fumigatus using agar well diffusion method and minimum inhibitory concentration. The antioxidant properties were carried out by DPPH and reducing power assays using various concentrations. Results: Results revealed that all pathogens were highly susceptible and inhibited by all solvent extracts. The methanolic and ethanolic leaves extracts exhibited promising antimicrobial activity and inhibited the growth of pathogens at par with the standard drugs viz., chloramphenicol for Bacteria and Fluconazole for fungi. Moreover, performance of methanolic and ethanolic extracts was the best amongst all solvents. In terms of antioxidant properties, both methods i.e., DPPH free radicals and reducing power resulted significant activity. Conclusion: The Phytochemical screening and biological activities of Teucrium stocksianum leaves extracts is reported for the first time. The ethanol, methanol, n-hexane and aqueous extracts of Teucrium stocksianum possess significant inhibitory effect against tested pathogens. The present investigation Teucrium stocksianum leaves extract contain potential antimicrobial components that may be of great use for the development of pharmaceutical industries as a therapy against various diseases. These results denote in-depth analysis of methanolic and ethanolic extracts to search potential compound responsible for antimicrobial activity. The results of the study support the folklore claim along with the development of new antimicrobial drugs from the plant. The results showed that Teucrium stocksianum leaves extracts possess multiple essential phytochemicals. Presence of phenolic compounds in plant extract demonstrates antioxidant activity. Both tests for antioxidant properties exhibited marked effects and can be employed as a potential natural antioxidant agent which may be used for mitigating oxidative stress. Nevertheless, there is need to explore mechanism involved for such kind of activity. The current findings hold up the ethno-pharmacological utilization of plant in the treatment of microbial infections and embrace great perception in the development of unusual antimicrobial and antioxidant agents.